OP0270-HPR Should A Successful Early Inflammatory Arthritis Clinic Also Address Cardiac Risk?. (10th June 2014) - Harrison, T.; Martin, L.; Barnabe, C.
Abstract : Background: RA patients have higher cardiovascular disease (CVD) risk. There is a 60% increase in the risk of death from cardiovascular causes compared with the general population and, survival rates for patients are significantly lower. It has been reported that rheumatologists feel CVD risk management is outside their domain. A resolution for this clinical issue is needed to prevent patients with RA from falling into a dangerous care gap. Objectives: To describe and determine the prevalence of CVD risk factors in an Early Inflammatory Arthritis (EIA) cohort, and to calculate 10-year CVD risk scores. A secondary objective was to compare the prevalence of CVD risk factors between EIA patients and the general Canadian population. Methods: A multidisciplinary Early Inflammatory Arthritis Clinic is held at our tertiary care centre in Canada, with a catchment area of 1.5 million people. Criteria for the clinic include a referral for symmetric polyarthritis. A standardized data collection protocol captures clinical data including the DAS28 and HAQ. Patients are seen every 3 months for the first year, and are treated to a low disease activity target. Demographic information, medications, traditional CVD risk factors (hypertension, dyslipidemia, obesity, smoking, diabetes and family history) and variables for Framingham (FRS) lipid, BMI and QRISK®2 10 year risk score calculators were extracted at the baseline visit (study period 01/2009 to 12/2012). Results: Our cohort includes 150 patients (62% female, 89% Caucasian, mean age 52 years), with 91% meeting 1987 ACR criteria and 96% meeting 2010 ACR/EULAR criteria for RA. The mean baseline DAS28 score was 5.17 (SD ± 1.31) with a mean tender joint count (28 joints) of 11 (SD ±7), swollen joint count of 8 (SD ±6) and HAQ 1.81 (SD ±0.87). DAS28 scores improved during the first year (3.61 at 6 months, 2.99 at 12 months) as did the HAQ score (0.72 and 0.55 respectively). A CVD risk score could only be calculated in 123 patients as not all patients had documentation of CVD risks. 89 patients (72%) had at least one CVD risk factor, 16 (13%) had two, 15 (12%) had three and 9 (7%) had more than three risk factors. The mean lipid FRS could be calculated for 47 patients: 12 (62%) were low risk, 29 (26%) were intermediate risk and 6 (13%) were high risk. The mean BMI FRS could be calculated for 122 patients: 71 (58.%) of patients were low risk, 29 (24)% were intermediate risk and 21 (17%) were high risk. QRISK®2 could be calculated for 52 patients 12 (23%) had high-risk scores of 20%. There were 3 cardiac events observed during the first year of disease; incidence rate 0.02/100 person-years. In comparison to the general population of Canada for four CVD risk factors 1, the EIA patients had up to 58% higher frequency of these risks. Conclusions: Patients in our EIA clinic with a diagnosis of rheumatoid arthritis are well managed from the perspective of their rheumatoid arthritis as evidenced by their DAS28 and HAQ scores at 6 and 12 months. However nearly half had intermediate to high FRS and QRISK risk scores, and much higher scores of cardiac risks compared to the Canadian population. Given these observations, the EIA clinic may be an ideal setting to both educate patients about cardiac risk and intervene in modifiable risk factors earlier in their disease. References: Public Health Agency of Canada. (2009). Tracking Heart Disease and Stroke in Canada, 2009. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4664